Magnetic oscillation of optical phonon in ABA- and ABC-stacked trilayer graphene - Jung, Jeil (2015)
We present a comparative measurement of the G-peak oscillations of phonon frequency, Raman intensity, and linewidth in the magneto-Raman scattering of optical E2g phonons in mechanically exfoliated ABA- and ABC-stacked trilayer graphene (TLG). Whereas in ABA-stacked TLG, we observe magnetophonon oscillations consistent with single-bilayer chiral band doublets, the features are flat for ABC-stacked TLG up to magnetic fields of 9 T. This suppression can be attributed to the enhancement of band chirality that compactifies the spectrum of Landau levels and modifies the magnetophonon resonance properties. The drastically different coupling behavior between the electronic excitations and the E2g phonons in ABA- and ABC-stacked TLG reflects their different electronic band structures and the electronic Landau level transitions and thus can be another way to determine the stacking orders and to probe the stacking-order-dependent electronic structures. In addition, the sensitivity of the magneto-Raman scattering to the particular stacking order in few-layer graphene highlights the important role of interlayer coupling in modifying the optical response properties in van der Waals layered materials.